British rock modernism, 1967-1977 : the story of music hall in rock - Faulk, Barry J. (Ashgate popular and folk music series., 2010)
British Rock Modernism, 19671977 explains how the definitive British rock performers of this epoch aimed, not at the youthful rebellion for which they are legendary, but at a highly self-conscious project of commenting on the business in which they were engaged. They did so by ironically appropriating the traditional forms of Victorian music hall and the result was a symbolically charged form whose main purpose was to unsettle the hierarchy that set traditional popular culture above the new medium.